(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Anoplophora malasiaca Thomson is recorded for the first time in ltaly. It is a xilophagous species present in Japan, Korea and Taiwan. lt’s a quarantine pest for Europe.